Agroforestry Application on Forest Land Under Stands System to Increase Reserved Food and Forest Sustainability at Pujon, Malang District - Triwanto, Joko (Technium Social Sciences Journal, 2022)
This research will produce a forest management model that can increase food reserves and the competitiveness of agricultural products from the use of forest land under stands, as an effort to increase food security. The research will be conducted in the production forest area of The State Forestry Public Company (Perhutani) BKPH Pujon KPH Malang Unit II, East Java from September 2020 to February 2021. The method of developing a management model is based on the level of land development. The analysis uses the Structural Equation Model (SEM) model with the help of the WarpPLS program (Partial Least Square development) which is able to accommodate reflective and formative indicators to test the effect between variables. Land use under stands carried out in the agroforestry model provides economic and environmental benefits, therefore, it was to be able to maintain forest sustainability. Profits from agroforestry on land under stands with intercropping of seasonal crops of vegetables and pulses B/C ratio = 1.77.